KETERAMPILAN MEMBACA DAN PRESTASI PADA MATA PELAJARAN BAHASA INDONESIA PESERTA DIDIK SEKOLAH DASAR - Putri, Sindy Olivia; Fradana, Ahmad Nurefendi (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2025)
The ability to read in understanding is the key to success for students in the learning process. Learners gain some knowledge through reading activities meaning that reading comprehension skills can be trained in all subjects at school. Reading comprehension has three stages that can be applied to the learning process towards the goal of reading comprehension, namely the reading stage, the reading stage and the post-reading stage. This research was conducted with the aim of knowing the role of reading comprehension in improving the performance of third grade elementary school students in Indonesian language subjects and the research method is a qualitative approach that uses a case study model observation and in-depth interviews have now been used as data collection techniques, as well as documentation, data analysis techniques include preparing cross-case analysis and drawing conclusions.